Sex-Related Differential Whole-Brain Input Atlas of Locus Coeruleus Noradrenaline Neurons - Sun, Pei; Wang, Junjun; Zhang, Meng; Duan, Xinxin; Wei, Yunfei; Xu, Fuqiang; Ma, Yan; Zhang, Yu-Hui (Frontiers in Neural Circuits, 2020)
As the most important organ in our bodies, the brain plays a critical role in deciding sex-related differential features; however, the underlying neural circuitry basis remains unclear. Here, we used a cell-type-specific rabies virus-mediated monosynaptic tracing system to generate a sex differences-related whole-brain input atlas of locus coeruleus noradrenaline (LC-NE) neurons. We developed custom pipelines for brain-wide comparisons of input sources in both sexes with the registration of the whole-brain data set to the Allen Mouse Brain Reference Atlas. Among 257 distinct anatomical regions, we demonstrated the differential proportions of inputs to LC-NE neurons in male and female mice at different levels. Locus coeruleus noradrenaline neurons of two sexes showed general similarity in the input patterns, but with differentiated input proportions quantitatively from major brain regions and diverse sub-regions. For instance, inputs to male LC-NE neurons were found mainly in the cerebrum, interbrain, and cerebellum, whereas inputs to female LC-NE neurons were found in the midbrain and hindbrain. We further found that specific subsets of nuclei nested within sub-regions contributed to overall sex-related differences in the input circuitry. Furthermore, among the totaled 123 anatomical regions with proportion of inputs >0.1%, we also identified 11 sub-regions with significant statistical differences of total inputs between male and female mice, and seven of them also showed such differences in ipsilateral hemispheres. Our study not only provides a structural basis to facilitate our understanding of sex differences at a circuitry level but also provides clues for future sexually differentiated functional studies related to LC-NE neurons.